The Crime of Causing Suicide (An Analytical Legal Study) - Ismail, Masoud Hamid (Journal of Legal and Political Studies, 2015)
Iraqi legislator did not criminalize the cause of suicide. Unlike Iraqi legislator, legislator Kurdistan offense of causing suicide, and when that stopped working to paragraph (1) of Article (408) of the Penal Code, under Law No. (42) For the year 2004. Through our study of the crime of causing suicide rea ched an all it is a positive or negative activity carried out by the offender intentionally would pay others to suicide or attempted. It is clear that this definition is causing suicidal intentional crime entails for having the presence of criminal intent has caused, regardless of the activity, whether positive or negative. This crime is the closest of the murder, it causes another suicide and deliberate paid to it, is closer to the killer of it to something else.
Keywords: criminalize; legislator; suicide; intentional crime